Chapter «Non deponeva mai dalle mani un librettino, ed il vocabulario della lingua cocincinese»: l'inedita relazione di viaggio di Domenico Fuciti (1623-1696) in terra vietnamita (Studi e saggi, 2021)
In addition to tracing the main aspects and the most salient events in the life of the Neapolitan Jesuit Domenico Fuciti (1623-1696), attention will be paid to the religious and socio-cultural issues that emerge from a critical reading of the unpublished Relazione della Missione, preserved in the Archivum Romanum Societatis Iesu (ARSI) of which the second chapter (central chapter) is published here. The historical coordinates regarding Fuciti's missionary activity and his hostility towards the Society for Foreign Missions of Paris, whose members were sent to the Indochinese peninsula by the Sacra Congregatio de Propaganda Fide, are also taken into consideration.